When Anxiety Outweighs Motivation: Motivational and Affective Predictors of EFL Achievement in Indonesian Vocational Schools - Dewa Sang Made Widiantara; Anak Agung Putri Maharani; I Gde Putu Agus Pramerta (Educazione: Journal of Education and Learning, 2026)
Cognitive ability alone does not determine success in learning English as a foreign language, since psychological factors strongly influence how students engage and perform. Research that examines these factors together within vocational education remains scarce. This study investigates intrinsic motivation, extrinsic motivation, and learning anxiety as predictors of EFL learning achievement among vocational high school students. A quantitative ex post facto design was applied to 137 students of SMKS Praja Pandawa Bangli, selected through total sampling. Data on the three predictors were collected using validated questionnaires, while achievement data were drawn from documented English scores. The data were analyzed through descriptive statistics and multiple linear regression. The results show that intrinsic motivation has a positive and significant effect on EFL learning achievement, whereas learning anxiety has a negative and significant effect. Extrinsic motivation, by contrast, shows no significant independent effect. Together, the three predictors account for 24.9 percent of the variance in student achievement. These findings indicate that internal psychological conditions matter more than external incentives in shaping language learning outcomes. From the perspective of transformational education and learning, the study suggests that meaningful change in EFL learning grows not from external pressure but from instruction that strengthens intrinsic motivation and dismantles emotional barriers, enabling students to move from passive compliance toward authentic and self-sustaining engagement with the language.